PLAIN AND GLAZED WARE FROM THE 6TH – EARLY 7TH C. POTTERY WORKSHOP AT LOZENETS RESIDENTIAL DISTRICT, SOFIA (PRELIMINARY REPORT) - Evelina Todorova (Приноси към българската археология)
The current paper aims at presenting the main pottery groups produced in the Early Byzantine pottery workshop found during rescue excavations at Lozenets residential district, Sofia, Bulgaria in 2000 – 2001. Three kilns, several pits related to them and a great amount of discarded wasted ceramics were found. The attempt to establish relative chronology of these structures and features showed that all of them functioned more or less simultaneously in a limited time span – the second half of the 6th – early 7th c. The same range of storage jars, plain and glazed table and kitchen wares were fired together in each one of the kilns. A wide variety of rim profiles was documented within every ceramic category, hinting to the magnitude of the production scale. All pottery groups fit perfectly within the Late Roman ceramic production tradition since they find close analogies with pottery discovered at other sites in the area from this period. Glazed pottery is very similar to vessels from the 4th – early 5th c., whose prototypes were produced in the Pannonian workshops. At the present moment the pottery workshop appears to be one of a kind for its period, evidencing how glazing pottery persisted since the Roman times and was passed down to the Early Middle Ages.